Takhrij and Syarah Hadith of Chemistry: Blowing Food and Drink - Risa Nurfadilah; Tuti Garnasih; Kifah Gibraltar Bey Fananie; Anggie Qory Alawiyah; Yusuf Rohmatulloh (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet about the prohibition of smoking hot food. This research method is qualitative through the approach of takhrij and sharah hadith with chemical analysis. The result and discussion of this research is that the prohibition of blowing hot food and drinks has been explained by Rasulullah Saw and can be described in the field of science as a result of blowing food and drinking heat. The conclusion of this research is takhrij and syarah hadith of the Prophet about blowing hot food and drinks with chemical analysis can cause health problems in the body.